Collections held by the National Library of Scotland relating to the British colonies (as filmed by the AJCP), [M1158-M1168, M1961-M1965] - Australian Joint Copying Project; National Library of Australia; Library of New South Wales (Canberra : Australian Joint Copying Project, 1724)
M1158-M1168: Selections from records in Catalogues 1-5 of the National Library of Scotland. Includes the papers of Henry Dundas, Gen. Sir George Brown, Admiral Sir Thomas Cochrane, Lord Stuart, Sir Walter Scott and Thomas Carlyle, and the publishers Archibald Constable and William and John Blackwood. There is also material on Thomas Muir, T.F. Palmer and the other Scottish Martyrs transported to Australia in 1793. Correspondents include Sir Edmund Barton, Sir Edward Braddon, Sir Thomas Brisbane, Sir James Brooke, Sir Hugh Clifford, Sir Charles Gavan Duffy, Lord Hopetoun, Alexander Maconochie, Lachlan Macquarie, Sir Henry Parkes, G.W. Rusden and Major Gen. R.H. Wynyard.
M1961-M1965: Selections from collections held by the National Library of Scotland relating to Australia, New Zealand, Java, Papua, Borneo, East Indies, Penang, Singapore, China and other countries. Principal collections include papers of: Sir Thomas Brisbane, 1856; Alexander Murray, 1911-1915; Admiral Charles Graham, 1845-47; typescripts by Robert L. Turner re Papua; General Sir Charles W. Pasley, 1855-61; William Scott of Raeburn, 1834-42; Sir Giblert Elliot, 1st Earl of Minto, 1803-1813; Gilbert Elliot, 2nd Earl of Minto, 1811-54; Rear-Admiral Robert K. Dickson, 1915-50 and Brig.-Gen. Alexander Walker, 1786-1826. Topics include business matters and life in Penang and Singapore, the Dardanelles Campaign, Maori War, N.S.W. in the early 1800s, military activities in Java ca. 1812; Sir John Franklin, Antarctic expeditions and other matters.
National Library of Australia holds microfilm master.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the Library of New South Wales.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Microfilmed from originals held at: National Library of Australia.
Microfilm copy of originals held by the National Library of Scotland, Edinburgh.
Keywords: Statesmen -- Great Britain -- Archives; Authors, Scottish -- 19th century -- Archives; Convicts -- Scotland -- Archives; Publishers and publishing -- Great Britain -- Archives